TRP Channels Localize to Subdomains of the Apical Plasma Membrane in Human Fetal Retinal Pigment Epithelium - Zhao, Peter Y. (Invest Ophthalmol Vis Sci, 2015)
PURPOSE. Calcium regulates many functions of the RPE. Its concentration in the subretinal space and RPE cytoplasm is closely regulated. Transient receptor potential (TRP) channels are a superfamily of ion channels that are moderately calcium-selective. This study investigates the subcellular localization and potential functions of TRP channels in a first-passage culture model of human fetal RPE (hfRPE). METHODS. The RPE isolated from 15- to 16-week gestation fetuses were maintained in serum-free media. Cultures were treated with barium chloride (BaCl(2)) in the absence and presence of TRP channel inhibitors and monitored by the transepithelial electrical resistance (TER). The expression of TRP channels was determined using quantitative RT-PCR, immunoblotting, and immunofluorescence confocal microscopy. RESULTS. Barium chloride substantially decreased TER and disrupted cell–cell contacts when added to the apical surface of RPE, but not when added to the basolateral surface. The effect could be partially blocked by the general TRP inhibitor, lanthanum chloride (LaCl(3), ~75%), or an inhibitor of calpain (~25%). Family member-specific inhibitors, ML204 (TRPC4) and HC-067047 (TRPV4), had no effect on basal channel activity. Expression of TRPC4, TRPM1, TRPM3, TRPM7, and TRPV4 was detected by RT-PCR and immunoblotting. The TRPM3 localized to the base of the primary cilium, and TRPC4 and TRPM3 localized to apical tight junctions. The TRPV4 localized to apical microvilli in a small subset of cells. CONCLUSIONS. The TRP channels localized to subdomains of the apical membrane, and BaCl(2) was only able to dissociate tight junctions when presented to the apical membrane. The data suggest a potential role for TRP channels as sensors of [Ca(2+)] in the subretinal space.